2001
DOI: 10.1111/j.1095-8649.2001.tb02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible modes of anadromy in Baltic sea trout: making the most of marginal spawning streams

Abstract: From examination of the ratios of strontium to calcium laid down as a lifetime record in the otoliths of sea trout Salmo trutta from Gotland, Baltic Sea, it was found that: (1) the shortest stream was used mostly by precociously emigrant or coastally hatched spawners; (2) longer streams had more fish that underwent normal smoltification; (3) sea-caught fish were predominantly coastally hatched (presumably near stream mouths). Furthermore, some otoliths showed no evidence of a freshwater history at all, raising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 17 publications
9
62
2
Order By: Relevance
“…For example, maternal transfer of elements to the progeny's calcified structures via yolk has been suspected (Brophy et al 2004, Ruttenberg et al 2005, Chittaro et al 2006; element enrichment was found in the cores of juvenile otoliths in several species of fish and it was speculated that, among other factors, the enrichment was due to maternal contributions of elements to the eggs. Building on work by Rieman et al (1994) and Limburg et al (2001) who initially investigated transgenerational marking, Thorrold et al (2006) provided conclusive evidence for the maternal transfer of elements via yolk. They injected both a benthic species and a broadcast spawning species of fish with 137 Ba and detected elevated levels of 137 Ba in the resulting progeny.…”
Section: Abstract: Statolith · La Icp-ms · Dispersal · Egg Source · mentioning
confidence: 99%
“…For example, maternal transfer of elements to the progeny's calcified structures via yolk has been suspected (Brophy et al 2004, Ruttenberg et al 2005, Chittaro et al 2006; element enrichment was found in the cores of juvenile otoliths in several species of fish and it was speculated that, among other factors, the enrichment was due to maternal contributions of elements to the eggs. Building on work by Rieman et al (1994) and Limburg et al (2001) who initially investigated transgenerational marking, Thorrold et al (2006) provided conclusive evidence for the maternal transfer of elements via yolk. They injected both a benthic species and a broadcast spawning species of fish with 137 Ba and detected elevated levels of 137 Ba in the resulting progeny.…”
Section: Abstract: Statolith · La Icp-ms · Dispersal · Egg Source · mentioning
confidence: 99%
“…Thus, it does not appear likely that occurrence of parr from both clusters in the creeks is caused by movement of young fish from their natal site to the place of collection. Records of migrating parr under one year of age do exist (Thorpe 1974;Bagliniére et al 1994;Limburg et al 2001), but such parr are reported to migrate in autumn-winter, after at least one growing season (Trophe 1974;Bagliniére et al 1994). We collected the young fish in late summer-early autumn; thus, the bulk of our samples should have been collected before such dispersal started.…”
Section: Spawning Sitesmentioning
confidence: 99%
“…4). Thus, the Sr:Ca ratios in otoliths can be used to reconstruct the migratory environmental history of the mullet, as for other fishes (Tzeng & Tsai 1994, Secor et al 1995, Secor & Rooker 2000, Limburg et al 2001.…”
Section: Sr:ca Otolith Ratios As Indicator Of Environmental Salinitymentioning
confidence: 99%
“…The ratios of strontium (Sr) to calcium (Ca) in otoliths are positively correlated to ambient salinities (Secor et al 1995, Tzeng 1996, Kawakami et al 1998. The temporal changes of Sr:Ca ratios in otoliths have been widely applied to determine the migratory environmental histories of diadromous fishes between freshwater and marine environments, including anadromous salmonids (Kalish 1990, Howland et al 2001, Limburg et al 2001, striped bass (Secor 1992, Secor & Piccoli 1996 and catadromous freshwater eels (Tzeng 1994, 1995, 1996, Tzeng & Tsai 1994, Tzeng et al 1997, 1999, 2000, 2002a, 2003, Tsukamoto & Arai 2001, Jessop et al 2002. Accordingly, the analysis of Sr:Ca ratios in otoliths, in combination with age data, makes possible the reconstruction of the migratory environmental history of the mullet and the clarification of its freshwater habitat use.…”
Section: Introductionmentioning
confidence: 99%